Methods for Obtaining Humus Substances: Advantages and Disadvantages - Anna M. Anielak; Renata Świderska-Dąbrowska; Dominika Łomińska-Płatek; Tomasz Dąbrowski; Krzysztof Piaskowski (Applied Sciences)
The paper reviews the patent descriptions of methods for obtaining humic substances and the procedures used in their industrial production. Selected humus substances, obtained using three different methods, were also examined. In the first one, humic substances were obtained due to the hydrolytic-oxidative decomposition of lignosulfonate. The second one consists of alkaline extraction from brown coal. According to the third, humus substances were extracted from digested sewage sludge. In the obtained humus substances, molecular composition, inorganic impurities, IR spectrum, gravimetric analysis, and the % shares of fulvic and humic acids were determined. The physico-chemical properties of the tested substances were also assessed. Based on the study’s results, the advantages and disadvantages of the obtained humus substances were determined, and methods for their modification to improve utility values were provided. Research on humic substances is a very important issue, especially concerning improving soil management and developing sustainable agricultural practices. They are key in improving soil structure and increasing its capacity to retain water and essential nutrients such as N, P, K, S, Ca, and Mg. In addition, humic substances are an important store of carbon in soils, which is important in the context of climate change.